Effect of keyhole characteristics on porosity formation during pulsed laser-GTA hybrid welding of AZ31B magnesium alloy. (June 2017) - Chen, Minghua; Xu, Jiannan; Xin, Lijun; Zhao, Zuofu; Wu, Fufa; Ma, Shengnan; Zhang, Yue
Abstract: This paper experimentally investigates the relationship between laser keyhole characteristics on the porosity formation during pulsed laser-GTA welding of magnesium alloy. Based on direct observations during welding process, the influences of laser keyhole state on the porosity formation were studied. Results show that the porosities in the joint are always at the bottom of fusion zone of the joint, which is closely related to the keyhole behavior. A large depth to wide ratio always leads to the increase of porosity generation chance. Keeping the keyhole outlet open for a longer time benefits the porosity restriction. Overlap of adjacent laser keyhole can effectively decrease the porosity generation, due to the cutting effect between adjacent laser keyholes. There are threshold overlap rate values for laser keyholes in different state. Highlights: Keyhole behavior has direct influence on porosity generation in weld joint. Large penetration depth increases porosity generation chance. Improvement of laser pulse overlap rate depresses the porosity formation.